Image contrast enhancement based on the intensity of regions’ pixels / Mahmood Salah Haithami - Mahmood Salah , Haithami (2018)
With digital cameras becoming more available and inexpensive instruments nowadays, capturing high definition photographs is made easier. Picture quality produced by digital cameras is affected by atmospheric changes, light conditions, quality of capturing devices, and operator expertise. Thus, image quality is heavily affected by the degree of variation in these factors, that its quality might degrade up to a point where image contrast enhancement is needed. Furthermore, improving the image’s contrast makes it easier to perceive features that were otherwise unviewable. Various methods were proposed to enhance the contrast. Most of the methods use either local or global statistical information of an image to produce a transformation function or multiple transformation functions, respectively. The prominent drawbacks of these methods are over/under enhancement or artifacts formation. These drawbacks are produced because images may have different regions and each region may require different degree of enhancement. To overcome the aforementioned drawbacks, an image contrast enhancement method based on the intensity of regions’ pixels is proposed. The proposed method consists of two steps: segmentation, and pixel value correction. The image is first segmented into regions based on the luminance and contrast level, then, for each region, contrast stretching with adaptive gamma correction are used to enhance the contrast. Qualitative and with quantitative results both demonstrate that the performance of the proposed method is better than other techniques in the field of image contrast enhancement.